Deficiency of Wdr60 and Wdr34 cause distinct neural tube malformation phenotypes in early embryos - Yan, Lu; Yin, Hailing; Mi, Yiwei; Wu, Yu; Zheng, Yufang (Frontiers in Cell and Developmental Biology, 2023)
Cilia are specialized organelles that extend from plasma membrane, functioning as antennas for signal transduction and are involved in embryonic morphogenesis. Dysfunction of cilia lead to many developmental defects, including neural tube defects (NTDs). Heterodimer WDR60-WDR34 (WD repeat domain 60 and 34) are intermediate chains of motor protein dynein-2, which play important roles in ciliary retrograde transport. It has been reported that disruption of Wdr34 in mouse model results in NTDs and defects of Sonic Hedgehog (SHH) signaling. However, no Wdr60 deficiency mouse model has been reported yet. In this study, piggyBac (PB) transposon is used to interfere Wdr60 and Wdr34 expression respectively to establish Wdr60PB/PB and Wdr34PB/PB mouse models. We found that the expression of Wdr60 or Wdr34 is significantly decreased in the homozygote mice. Wdr60 homozygote mice die around E13.5 to E14.5, while Wdr34 homozygote mice die around E10.5 to E11.5. WDR60 is highly expressed in the head region at E10.5 and Wdr60PB/PB embryos have head malformation. RNAseq and qRT-PCR experiments revealed that SHH signaling is also down-regulated in Wdr60PB/PB head tissue, demonstrating that WDR60 is also required for promoting SHH signaling. Further experiments on mouse embryos also revealed that the expression levels of planar cell polarity (PCP) components such as CELSR1 and downstream signal molecule c-Jun were down-regulated in WDR34 homozygotes compared to wildtype littermates. Coincidently, we observed much higher ratio of open cranial and caudal neural tube in Wdr34PB/PB mice. CO-IP experiment showed that WDR60 and WDR34 both interact with IFT88, but only WDR34 interacts with IFT140. Taken together, WDR60 and WDR34 play overlapped and distinct functions in modulating neural tube development.